The Mediating Role of Job Satisfaction in the Relationship between Human Resource Information Systems and Employee Performance at The Project Deployment Center Division of PT Len Industri (Persero) - Salsabila, Diva Elia; Askolani, Askolani; Rofaida, Rofi (The International Journal of Business Review (The Jobs Review), 2024)
Purpose – This study aimed to determine the mediating role of job satisfaction in the relationship between human resource information systems and employee performance in the Project Deployment Center Division of PT Len Industri (Persero).Design/methods/approach – This research uses a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 75 employees in the PDC division. The sampling technique used a simple random sampling technique and the data was analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique with SmartPLS software.Findings – The findings indicate that HRIS has a positive impact on job satisfaction, which in turn improves employee performance. This study shows that job satisfaction is a significant mediator in the relationship between HRIS and employee performance, suggesting that HRIS implementation can lead to better performance outcomes through improved job satisfaction.Research implications/limitations – The research implications suggest that organizations should invest in HRIS to improve job satisfaction and employee performance. However, the study is limited to a single division within a specific company, which may affect the generalizability of the findings. Future research could expand the scope to include multiple divisions or different organizations to validate the results.Originality/value – This study contributes to the existing literature by highlighting the importance of job satisfaction as a mediator in the relationship between HRIS and employee performance. It provides valuable insights for organizations seeking to enhance employee performance through technological advancements in human resource management